Chronicling Angry Bishops: On the Use and Perceptions of Episcopal Anger in 13th-Century Scandinavian Narratives - Boye, Sveinung K (Collegium Medievale, 2016)
Recent interest in what Stephen D. White, in an influential article from 1998, called "the politics of anger" has resulted in many articles and books about the anger of kings and the lay aristocracy across Europe. However, very little research has been done on the anger of bishops. Idealized bishops are generally portrayed as mild and humble rather than hot tempered, but this article argues, on the basis of Danish and Norwegian narra-tive sources, that anger nevertheless was an important political signal used by bishops as well. Through an analysis of Exordium Monasterii Carae Insulae (Øm Abbey Chronicle), Vita Gunneri episcopi Viborgensis (The Life of Bishop Gunner), Gesta Danorum and Hákonar saga Hákonarsonar (The Saga of Håkon Håkonsson), the article also argues that it is pos-sible to distinguish at least two different discourses of episcopal anger.